Different clusters of perfectionism in inpatients with anorexia nervosa and healthy controls. Issue 5 (3rd September 2022) - Longo, Paola; Aloi, Matteo; Delsedime, Nadia; Rania, Marianna; Segura Garcia, Cristina; Abbate-Daga, Giovanni; Marzola, Enrica
ABSTRACT: Perfectionism is a risk and maintaining factor for anorexia nervosa (AN) but studies on its classification are lacking. This study aimed to classify patients with AN and healthy controls (HCs) according to their perfectionism; to evaluate the association between perfectionism clusters and severity of general and eating psychopathology for both groups; to investigate the relationship between baseline perfectionism and hospitalization outcome for patients. A sample of 207 inpatients with AN and 292 HCs completed: Eating Disorders Inventory-2, Frost Multidimensional Perfectionism Scale, Beck Depression Inventory, and State- Trait Anxiety Inventory. Cluster analyses were run to classify participants according to their perfectionism scores. Three clusters (i.e., high, medium, low perfectionism) emerged for both patients with AN and HCs. The high perfectionism cluster was over-represented among patients. Both groups reported significant differences across clusters in eating-related difficulties. In AN, anxiety and depression severity varied across clusters according to perfectionism, but patients' baseline perfectionism was unrelated to hospitalization outcome. Inpatients with AN and HCs could be grouped in clusters of high, medium, and low perfectionism which also mirrored their eating psychopathology severity. Finally, hospitalization outcome was unrelated to inpatients' baseline perfectionism.